Use of The Wheel Model Evaluation in Outing Class Activities to Improve Children's Religious and Moral Learning Achievements at 'Aisyiyah Al Amin Kindergarten in Surakarta - Sugiyanti, S; Anshori, Ari; Maksum, Muh. Nur Rochim (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine in depth the use of the wheel model evaluation in outing class activitiesto improve children's religious and moral learning outcomes. The research methodused is a literature study. The results of the study indicate that the use of the wheel model evaluation in outing class activities provides a strong and flexible framework that significantly improves learning outcomes. Its success is highly dependent oncareful implementation, adequate planning, and the integration of assessment methodsthat are in line with the objectives of the activities outside the classroom.